2017
DOI: 10.1590/1414-431x20176409
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy and safety of contact force-sensing catheter and second-generation cryoballoon ablation for atrial fibrillation: a meta-analysis

Abstract: This meta-analysis compared the efficacy and safety of the contact force (CF)-sensing catheter and second-generation cryoballoon (CB) ablation for treating atrial fibrillation (AF). Six controlled clinical trials comparing ablation for AF using a CF-sensing catheter or second-generation CB were identified from PubMed, EMBASE, Cochrane Library, Wanfang Data, and China National Knowledge Infrastructure. The procedure duration was significantly lower in the CB group compared with that in the CF group [mean differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Recent meta‐analysis including 7,195 patients from 16 studies showed that as compared with RF ablation, cryoablation presented a comparable mid‐ and long‐term arrhythmia‐free survival and similar procedure‐related events . These results were also consistent when cryoballoon was compared with contact force RF catheter …”
Section: Cryoballoon Versus Rf Cathetermentioning
confidence: 60%
“…Recent meta‐analysis including 7,195 patients from 16 studies showed that as compared with RF ablation, cryoablation presented a comparable mid‐ and long‐term arrhythmia‐free survival and similar procedure‐related events . These results were also consistent when cryoballoon was compared with contact force RF catheter …”
Section: Cryoballoon Versus Rf Cathetermentioning
confidence: 60%
“…The post‐ablation use of AADs might be a confounder; however, those were not statistically associated with AF/AT recurrence. Several meta‐analysis reports have shown a contact force‐guided PVI and balloon‐based ablation significantly improved the AF freedom rate 35,36 . The PAF patients in this study underwent a contact force‐guided PVI or balloon ablation.…”
Section: Discussionmentioning
confidence: 86%
“…Several meta‐analysis reports have shown a contact force‐guided PVI and balloon‐based ablation significantly improved the AF freedom rate. 35 , 36 The PAF patients in this study underwent a contact force‐guided PVI or balloon ablation. Therefore, our results might support a high success rate with PVI methods achieving a durable PVI in PAF patients even when extending the ablation indication to a remodeled LA.…”
Section: Discussionmentioning
confidence: 99%
“…(Adapted from figures provided by Medtronic Inc.) pulmonary complications. Compared to the first-generation, the second-generation cryoballoon is associated with a higher incidence of these complications [32][33][34][35] .…”
Section: Safety Cryoballoon Pvimentioning
confidence: 99%